Effects of cannabinoid and vanilloid receptor antagonists on nicotine induced relaxation response enhancement in rabbit corpus cavernosum - İsmail Mert Vural; Gokce Sevim Ozturk Fincan; Derya Sebile Koc; Yagmur Okcay; Celil İlker Askin; Ayse Kubra Kibar; Sevil Ozger Ilhan; Yusuf Sarioglu (Iranian Journal of Basic Medical Sciences, 2022)
Objective(s): Endocannabinoids and nicotine regulate the neurotransmitter release in different central and peripheral synapses. Various studies in the literature demonstrate the interaction between endocannabinoid and nicotinic systems, especially in the central nervous system. The interaction between nicotinic and endocannabinoid systems was investigated in this study. We aimed to show the effects of cannabinoid and vanilloid receptor antagonists on nicotine-induced relaxation response increases in rabbit corpus cavernosum.Materials and Methods: From a total of seven male albino rabbits, three or four equal strips were cut from each corpus cavernosum and inserted in isolated organ baths. Tissues were contracted with phenylephrine (3×10−5 M). After contraction reached a plateau, strips were stimulated with EFS, and with the stabilization of EFS relaxation responses, 10-4  M of nicotine was administered to tissues. After that, in order to investigate the effects of AM251 (CB1 antagonist), AM630 (CB2 inverse agonist) or capsazepine (a vanilloid receptor antagonist) were given to different tissues, after the resting period.Results: Nicotine (10−4 M) increased the EFS-induced relaxation responses (14.60%±2.94%, P<0.05). AM630 decreased the enhancement of nicotine-induced EFS relaxation responses (nicotine 10-4 M enhancement: 17.16%±3.19%; nicotine 10-4 M enhancement in the presence of AM630 10-6 M: 4.44%±3.43% P<0.05; n=6), whereas effects of AM251 and capsazepine were not significant. Conclusion: In the present study, nicotine increased the amplitudes of EFS-induced relaxation responses probably via nicotinic acetylcholine receptors located on the nitrergic nerves of the corpus cavernosum. We showed the role of cannabinoid-like endo-ligands in nicotine-induced enhancement via CB2 receptors but not CB1 and VR1 receptors.